The handbook of clinical techniques in pediatric dentistry - Soxman, Jane A. (Ames, Iowa : John Wiley & Sons, Inc., 2015)
The Handbook of Clinical Techniques in Pediatric Dentistry provides the clinician with an increased level of expertise and skills for timely identification and intervention for various presentations in the developing dentition. It also clearly describes procedures for treatment in the primary and young permanent dentitions, including pulp therapy for primary and young permanent molars, extractions, space maintenance, and more. The most commonly encountered treatment needs are discussed with the goal of increasing clinician and staff confidence while decreasing chair-time and stress.With an emp.
Interim therapeutic restoration in the primary dentition / Jane A. Soxman -- Local anesthesia for the pediatric patient / Jane A. Soxman and Stanley Malamed -- Primary incisor restoration / Ari Kupietzky -- Primary molar adhesive tooth restoration / Constance M. Killian and Theodore P. Croll -- Full coverage restoration for primary molars / Jane A. Soxman -- Vital pulp therapy for primary molars / Jane A. Soxman -- Pulpectomy in primary teeth / James A. Coll -- Extraction of primary dentition / Jane A. Soxman -- Sealants / Jane A. Soxman and Patrice B. Wunsch -- Indirect pulp therapy for young permanent molars / Patrice B. Wunsch -- Direct pulp therapy for young permanent molars / Patrice B. Wunsch -- Diagnosis and treatment of molar-incisor hypomineralization / J. Timothy Wright -- Ectopic eruption of maxillary permanent molars / Ari Kupietzky and Jane A. Soxman -- Ectopic eruption of maxillary permanent canines / Jane A. Soxman -- Infraocclusion of mandibular primary molars / Jane A. Soxman -- Space maintenance / Jane A. Soxman -- Pulpal treatment in young permanent incisors following traumatic injury / Joe H. Camp -- Reattachment of permanent incisor enamel fragments / Jane A. Soxman -- Non-nutritive sucking and parafunctional habits / Jane A. Soxman -- Behavior guidance / Jane A. Soxman.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dental Care for Children -- methods; Pediatric Dentistry -- methods; Tooth Diseases -- therapy; Pedodontics; MEDICAL / Surgery / General; Pedodontics; Dentistry; Pedodontics; Youth -- Dental care; Electronic books; Electronic books